Application of the Al-Miftah Al-Ulum Method in Learning the Kitab Kuning Islamic Boarding Schools - Hendrisab, Hendrisab; Samsurizal, Samsurizal; Ringgit, Awang (Ahlussunnah: Journal of Islamic Education, 2022)
In fact, in several Islamic boarding schools, the majority can only read the kitab kuning after entering the aliyah class and even then only a small percentage. This research aims to determine the application of the Al-Miftah Lil 'Ulum method at Madrasah Tarbiyah Islamiyah Canduang both in terms of planning, steps, evaluation and supporting and inhibiting factors. This research is field research using a qualitative descriptive approach. Data collection was carried out by observing, interviewing, documenting and analyzing data. The results of this research can be concluded as follows: i) planning for the implementation of the Al-Miftah Lil 'Ulum method at Madrasah Tarbiyah Islamiyah Canduang was carried out by designing a program: sending teachers to participate in method training, facilitating all matters related to the method, forming a team responsible for the method , implementing the method with a pilot project program, appointing a method team coordinator, ii) the team holds various forms of activities such as material competitions, nazhom al-Miftah Lil 'Ulum and book reading practice. iii) hold tests after every chapter, semester exams, demonstrations, graduations. Fourth, the supporting factors for implementing the Al-Miftah Lil 'Ulum method at Madrasah Tarbiyah Islamiyah Canduang are: The school fully supports the Al-Miftah program with a pilot project program system, class 1 Madrasah Tarbiyah Islamiyah Canduang is a class for beginners to learn the basics.